Metabolomics as a Potential Chemotaxonomical Tool: Application in the Genus Vernonia Schreb - Martucci, Maria Elvira Poleti; De Vos, Ric C. H.; Carollo, Carlos Alexandre; Gobbo-Neto, Leonardo (PLOS ONE, 2014)
The taxonomic classification of the genus Vernonia Schreb is complex and, as yet, unclear. We here report the use of untargeted metabolomics approaches, followed by multivariate analyses methods and a phytochemical characterization of ten Vernonia species. Metabolic fingerprints were obtained by accurate mass measurements and used to determine the phytochemical similarities and differences between species through multivariate analyses approaches. Principal component analysis based on the relative levels of 528 metabolites, indicated that the ten species could be clustered into four groups. Thereby, V. polyanthes was the only species with presence of flavones chrysoeriol-7-O-glycuronyl, acacetin-7-O-glycuronyl and sesquiterpenes lactones piptocarphin A and piptocarphin B, while glaucolide A was detected in both V. brasiliana and V. polyanthes, separating these species from the two other species of the Vernonanthura group. Species from the Lessingianthus group were unique in showing a positive response in the foam test, suggesting the presence of saponins, which could be confirmed by metabolite annotation. V. rufogrisea showed a great variety of sesquiterpene lactones, placing this species into a separate group. Species within the Chrysolaena group were unique in accumulating clovamide. Our results of LC-MS-based profiling combined with multivariate analyses suggest that metabolomics approaches, such as untargeted LC-MS, may be potentially used as a large-scale chemotaxonomical tool, in addition to classical morphological and cytotaxonomical approaches, in order to facilitate taxonomical classifications.